A study on the proportion of unsuccessful exclusive breastfeeding and its associated factors among health care providers in Hospital Universiti Sains Malaysia - Hashim, Saodah (2017)
BACKGROUND Breastfeeding is widely recognized as the optimal and natural form of infant feeding. However, there are many obstacles and barriers towards exclusive breastfeeding to the recommended six months duration for mother to practice it. The aim of our study was to identify associated factors for unsuccessful exclusive breastfeeding among healthcare providers in Hospital Universiti Sains Malaysia. METHODS This cross-sectional study was conducted from June 2015 to December 2015 by using a validated Malay version structured self-administered questionnaire to 295 healthcare providers. The selected socio-demographics and maternal characteristics were obtained. Multiple logistic regressions were used to evaluate the associated factors for unsuccessful exclusive breastfeeding.RESULT The prevalence of unsuccessful exclusive breastfeeding among healthcare providers in Hospital Universiti Sains Malaysia was reported to be 58.3%. Mothers who deliver via Lower Segment Cesarean Section (OR 2.31[95% CI: 1.07, 4.98]), had inadequate breast milk (OR 4.06 [95% CI: 2.40, 6.89]) and mothers who preferred formula milk (OR 4.40 [95% CI: 1.45, 13.31]) were significantly associated with unsuccessful exclusive breastfeeding. CONCLUSION Unsuccessful exclusive breastfeeding among healthcare providers was high. Mode of delivery, adequacy of breast milk and mothers preference for infant feeding showed a significant positive association with unsuccessful exclusive breastfeeding.